2021
DOI: 10.3390/foods10061419
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on the Molecular and Physicochemical Changes of Protein and Starch of Wheat Flour during Heating

Abstract: The behaviors of starch and protein in wheat flour during heating were investigated, and the molecular changes of starch and protein and their effects on the textural characteristics were assessed. The results showed that with the increased temperature, soluble protein aggregated to insoluble high-molecular-weight protein polymers when the heating temperature exceeded 70 °C, and the aggregation of protein was mainly caused by covalent bonds of disulfide (SS) bonds. Hydrophobic interaction was the main noncoval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 33 publications
(37 reference statements)
0
3
0
Order By: Relevance
“…The change and specific role of gluten and HMW-GS during baking remained unclear. In this study, gluten polymerization was observed during biscuit baking, accompanied by the significant increase of the SDS-I level; this was evidently attributed to the heat-induced crosslinking reaction of protein during baking . Gluten polymerization is due to the oxidation of the free SH groups of cysteine and/or SH-SS interchange reactions.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…The change and specific role of gluten and HMW-GS during baking remained unclear. In this study, gluten polymerization was observed during biscuit baking, accompanied by the significant increase of the SDS-I level; this was evidently attributed to the heat-induced crosslinking reaction of protein during baking . Gluten polymerization is due to the oxidation of the free SH groups of cysteine and/or SH-SS interchange reactions.…”
Section: Discussionmentioning
confidence: 64%
“…In this study, gluten polymerization was observed during biscuit baking, accompanied by the significant increase of the SDS-I level; this was evidently attributed to the heat-induced crosslinking reaction of protein during baking. 31 Gluten polymerization is due to the oxidation of the free SH groups of cysteine and/or SH-SS interchange reactions. Free SH groups of cysteine on the peptide chain of glutenin and gliadin undergo oxidation reaction to from SS bonds, and the cysteine residues are converted into cystine residues, which refer to the free SH oxidation reaction.…”
Section: ■ Discussionmentioning
confidence: 99%
“…The upper rates of G ′ and G ′′ of SCD24_C reflect the formation of a more rigid structure compared to the untreated samples R, indicating molecular interactions and structural modifications caused by heat treatment, and that could form a high-density three-dimensional network of cross-linked proteins and starch when gelatinization occurs. Probably, the macroscopic expression was the consequence of microlevel changes of starch and protein [ 57 ].…”
Section: Resultsmentioning
confidence: 99%